The emotional impact of the Covid-19 pandemic in women facing infertility - Galhardo, Ana (2022)
People facing infertility are inevitably affected by COVID-19 pandemic, having to delay their parental projects. This study aimed to explore the emotional impact (depression and anxiety symptoms and perceived stress) of the COVID-19 pandemic in Portuguese women pursuing assisted reproductive technology (ART). Results showed 67.4% of participants were in confinement but were dealing with it in a reasonably positive way. Women who continued to work at their workplace presented significantly higher levels of depressive and anxiety symptoms than those who stayed at home. No significant differences were found regarding depression and anxiety symptoms scores when comparing the current sample with an infertility reference sample and a community sample. Depressive and anxiety symptoms remained stable, but there was a significant decrease in perceived stress over the eight-week period. Although these findings do not suggest a worsening of psychological difficulties due to the COVID-19 pandemic, health professionals should be attentive to patients' long-term psychological consequences. It may be helpful to provide additional psychological support to women when restarting their ART treatments.